Development of Question Answering System for Public Relation Division in Student Admission - Lutfi Rahmatuti Maghfiroh; Wahyudi Syahputra; Ibnu Santoso (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
Politeknik Statistika STIS (Polstat STIS) holds the new students' admission (PMB) every year which aims to gather, test, and, select all of its applicants who want to continue their study at STIS. STIS establish a committee during this event named Public Relation (PR) Division. PR Division to be intermediaries between STIS and the applicants. One of many PR Division tasks is to reply to all the questions from applicants about administration, procedure, or other things about PMB and STIS. PR Division is facing some problems that can hinder its performance to do the tasks. How do we address the problem is the reason that this research begins in the first place. The goal of this research is to build and establish a web-based system that is capable to solve all the problems the current system has. The system is divided into two main functions, the first one is FAQ management by PR Division members. The other function is a chatbot that automatically answers the question by using the TF-IDF algorithm. The conclusion on all testing and evaluation is the system that being build is already fulfilled all its requirements also the system is feasible to be used.